Strategies of Electronic Financial Services Development in Bulgaria - Trifonova, Silvia (Research Papers, 2005)
The main objective of this research is to analyze the electronic financial services development in Bulgaria, with focus on the role and application of the strategic analysis in the field of electronic banking. The principal arguments for this research are associated with the very fast penetration of modern information and communication technologies in the economy and business, and substantial development of financial intermediation in Bulgaria. On this basis, the current analysis needs to explore and assess the fundamental changes passing nowadays in the payment infrastructure, national payment system and banking technological development.The current research was focused on the contemporary trends in the electronic banking development in Bulgarian practice, the payments executed via Internet and the National card payment system BORICA. These topics were analyzed by the point of view of their specific features and in the context of their principal operational interrelationships. Profound analysis was made of the particular electronic financial services, provided by the commercial banks in Bulgaria. Moreover, the study comprises a research on the relevant strategies, aims and techniques applied by the financial institutions in order to meet the contemporary business challenges in the banking sector.